Некоторые тенденции морфологической эволюции в подсемействе Harmolitinae (Hymenoptera, Eurytomidae) - Зерова, М.Д. (Вестник зоологии, 1971)
Investigation of some species of the subfamily Harmolitinae is a subject of the
article. When studying their comparative morphology some regularities were found out
which were of use in tracing the evolutionary trends of this subfamily, and those of the
family Eurytomidae.
The evolution seemed to be directed from the primitive and large forms with a long
elongated body, long subquadrate pronotum, coarse sculpture of head and thorax, and female antennae with not defferentiated club — to the smaller forms with smooth and shining
sculpture, rather short pronotum and last funicular joint fused in a club.
Such tendency in morphological specialization was also observed in some families
of Chalcidoidea and other parasitic Hymenoptera, particulary in Proctotrupoidea.